2018
DOI: 10.1007/s12194-018-0472-3
|View full text |Cite
|
Sign up to set email alerts
|

Automated prediction of dosimetric eligibility of patients with prostate cancer undergoing intensity-modulated radiation therapy using a convolutional neural network

Abstract: The quality of radiotherapy has greatly improved due to the high precision achieved by intensity-modulated radiation therapy (IMRT). Studies have been conducted to increase the quality of planning and reduce the costs associated with planning through automated planning method; however, few studies have used the deep learning method for optimization of planning. The purpose of this study was to propose an automated method based on a convolutional neural network (CNN) for predicting the dosimetric eligibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…PCa does not have the same characteristics and severity in an Afro-American or Asian population [103]. Yet, most of the previously reviewed studies are based on Asian populations [20,26,28,37,42,50,59] and are probably not applicable to an African American population. Heintzelman [63] emphasizes this difference by showing that Afro-American patients in their study were clustered at the upper end of the pain index spectrum, even if these results were not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCa does not have the same characteristics and severity in an Afro-American or Asian population [103]. Yet, most of the previously reviewed studies are based on Asian populations [20,26,28,37,42,50,59] and are probably not applicable to an African American population. Heintzelman [63] emphasizes this difference by showing that Afro-American patients in their study were clustered at the upper end of the pain index spectrum, even if these results were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Nicolae et al [58] demonstrated that compared to brachytherapists, ML helped to reduce radiotherapy planning time from a mean time of 18 min to shorter than 1 min with no significant difference regarding irradiated prostate volume. Kajikawa et al [59] built two CNN algorithms for optimization radiotherapy planning. With a CNN model trained with anatomical structure label dataset, the algorithm led to more contrasting results, with 70% accuracy for predicting the dosimetric eligibility of patients treated with intensity-modulated radiation therapy (IMRT).…”
Section: Radiotherapymentioning
confidence: 99%
“…Dose estimation was also the aim of Kajikawa et al. who investigated the feasibility of DL in the automated determination of dosimetric eligibility of prostate cancer patients undergoing intensity‐modulated radiation therapy …”
Section: Application Areas In Radiological Imaging and Radiation Therapymentioning
confidence: 99%
“…Deep learning based methods have been studied for multiple tasks in medical imaging and radiation therapy including segmentation [2] and classification [3]. Other knowledge based methods are employed to optimize beam related parameters in intensity modulated radiation therapy (IMRT) [4,5] or to optimize beam orientations, positions, shapes, and weights directly (direct aperture optimization).…”
Section: Problemmentioning
confidence: 99%